ANALISIS KESULITAN BELAJAR SISWA BERDASARKAN TEORI NEWMAN DALAM PEMECAHAN MASALAH PENGUKURAN VOLUME KELAS IV DI MADRASAH IBTIDAIYAH - Herlina Wulandari; Riawan Yudi Purwoko; Muflikhul Khaq (Jurnal Binagogik, 2024)
This research aims to determine learning difficulties based on Newman's theory in solving problemsmeasuring volume in class IV at madrasah ibtidaiyah. This research is a type of descriptive qualitativeresearch. This research was conducted at MI Muhammadiyah Krendetan. The technique for selectingresearch subjects uses the purposive sampling method. The subjects were selected by 4 students basedon the results of the teacher's consideration based on the test results and how to work according to thedifficulties that will be taken up in the research. Data collection techniques use tests, observation,interviews and documentation. The data analysis techniques used are data reduction, data presentation,and drawing conclusions. The results of this research can be concluded that: 1) The reading difficultystage students do not experience difficulty in reading, 2) The difficulty understanding stage studentsexperience errors in writing "known" and "asked" in questions, 3) The transformation difficulty stagestudents experience errors in writing calculating operations, 4) Stage of difficulty in processing skills,students experience errors because they do not write down how to do it, students have difficulty incalculating, and students do not continue the process of doing it, 5) Stage of difficulty in writing thefinal answer, students have difficulty in writing conclusions, students are not correct in the finalanswer, and students combine the conclusions with the way they work. This research found difficultiesbased on Newman's theory, namely that students had difficulty understanding, transforming,processing skills and writing final answers. Therefore, it is important to anticipate so that students donot experience difficulties in solving similar problems.